A REVIEW OF SOIL DEVELOPMENT IDENTIFICATION IN INDONESIA BASED ON FREE SWELLING INDEX - Maulani, Tika Febriayu; Putri, Christy Anandha (INDONESIAN JOURNAL OF CONSTRUCTION ENGINEERING AND SUSTAINABLE DEVELOPMENT (CESD), 2025)
Expansive soil is a type of clay that undergoes significant volume changes due to changes in moisture content, and can cause serious damage to construction if not identified at the planning stage. This research aims to review the identification method of expansive soil development degree in Indonesia through a literature study of six previous studies. The analysis was based on the type of test, soil physical parameters, sample location, and classification criteria used, such as Chen (1975), Raman (1967), Seed (1962), and other standards. The review showed that the majority of studies relied on indirect approaches, such as Atterberg Limit testing and grain gradation analysis, which generally resulted in medium to very high classifications. However, there are inconsistencies between the results of indirect and direct methods. One of the direct methods that has been introduced is the Free Swelling Index (FSI) based on the Indian standard IS: 2720-40 (1977), which is considered simple, fast and applicable, but is still rarely used in Indonesia. Therefore, this study recommends the application of the two approaches and the utilization of FSI as a more accurate and efficient alternative for the initial identification of expansive soils.